2019
DOI: 10.1186/s12905-019-0847-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between menopausal symptoms and burnout. A cross-sectional study among nurses

Abstract: BackgroundDespite the growing presence of menopausal women in workplaces, studies aimed at exploring the link between menopausal symptoms and job well-being are scarce. In the interest of addressing this gap, the present study aimed to explore whether menopausal symptoms might contribute to increased levels of burnout and whether this relationship can be moderated by social or personal resources.MethodThe study design was cross-sectional and non-randomized. Ninety-four menopausal nurses completed a self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 66 publications
1
27
0
2
Order By: Relevance
“…Menopausal symptoms such as lack of energy and fatigue, experienced by 43.9-64.7% of menopausal women, are strongly associated with exhaustion and burnout, which may seriously compromise quality of life of affected women [22][23][24]. Fatigue is described as a feeling of lack of energy, weariness, loss of drive, decrease or loss of ability to sustain even routine activities, overwhelming feeling of tiredness, exhaustion, and physical or mental strain that occurs even without conspicuous effort.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Menopausal symptoms such as lack of energy and fatigue, experienced by 43.9-64.7% of menopausal women, are strongly associated with exhaustion and burnout, which may seriously compromise quality of life of affected women [22][23][24]. Fatigue is described as a feeling of lack of energy, weariness, loss of drive, decrease or loss of ability to sustain even routine activities, overwhelming feeling of tiredness, exhaustion, and physical or mental strain that occurs even without conspicuous effort.…”
Section: Introductionmentioning
confidence: 99%
“…Pathological fatigue is an intensified level of the common "physiological" fatigue, and it may be evoked by pervasive pathologies [24][25][26]. The relation between fatigue and stress is dynamic, and it drastically changes during menopausal transition [22]. In fact, chronic fatigue in humans is described as a stress-related condition that involves numerous systemic dysfunctions, which alter homeostasis and hinder women's ability to bounce back from either fatigue or distress [5,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to an increased involvement of middle-age women in the workforce [13]. Various studies have revealed that menopausal symptoms predominantly affect women in the workforce than those out of the workforce [14][15][16][17]. This might be due to an increase in work stress and working environment [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, iron dysregulation—as indicated by exceptionally high serum ferritin levels—is common in AD patients; it contributes to oxidative stress and causes virulent reactivation of dormant blood and tissue microbiome [ 39 ]. E. coli bacterial lipoproteins act as agonists of toll-like receptor (TLR) 2 and nucleotide-binding domain and leucine-rich repeat containing protein 3 (NLRP3); they induce inflammation and increase cytokine production through their interaction with recombinant human Serum Amyloid A1 (hSAA1) [ 47 ]. In addition, various levels of bacterial LPS have been detected in blood samples and brain lysates from the superior temporal lobe neocortex and hippocampus of AD patients.…”
Section: The Mechanism Underlying Ad Developmentmentioning
confidence: 99%